2020
DOI: 10.1103/physrevb.102.144524
|View full text |Cite
|
Sign up to set email alerts
|

Second group of high-pressure high-temperature lanthanide polyhydride superconductors

Abstract: Rare-earth polyhydrides formed under pressure are promising conventional superconductors, with the critical temperature Tc in compressed LaH10 almost reaching room temperature. Here, we report a systematic computational investigation of the structural and superconducting properties of rare-earth (RE) polyhydrides formed under pressure across the whole lanthanide series. Analyses of the electronic and dynamical properties and electron-phonon coupling interaction for the most hydrogen-rich hydrides REHn (n = 8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(105 citation statements)
references
References 50 publications
5
100
0
Order By: Relevance
“…For example, Fm � 3m YbH 10 was calculated to have a T c that was about a factor of two smaller than isotypic LaH 10 at the same pressure. [29] Although it is likely that the evolution of the geometric properties, electronic structure and bonding within I4=mmm BaH 4 would be similar to our findings for CaH 4 and SrH 4 this phase was not studied because unlike the other hydrides discussed in this section, this compound does not lie on the convex hull. [75] Moreover, the only polyhydrides of barium that have been made under high pressure are Ba 8 H 46 [76] and BaH 12 .…”
Section: Divalent Metalssupporting
confidence: 51%
See 3 more Smart Citations
“…For example, Fm � 3m YbH 10 was calculated to have a T c that was about a factor of two smaller than isotypic LaH 10 at the same pressure. [29] Although it is likely that the evolution of the geometric properties, electronic structure and bonding within I4=mmm BaH 4 would be similar to our findings for CaH 4 and SrH 4 this phase was not studied because unlike the other hydrides discussed in this section, this compound does not lie on the convex hull. [75] Moreover, the only polyhydrides of barium that have been made under high pressure are Ba 8 H 46 [76] and BaH 12 .…”
Section: Divalent Metalssupporting
confidence: 51%
“…[71] Similarly, a recent study on the REH 8 , REH 9 and REH 10 concluded that a high T c in these phases is correlated with a large number of hydrogenic, and low number of RE f states at E F . [29] In the sections that follow, we will discuss the evolution of the structure, electronic structure and propensity for superconductivity in these phases under pressure. To gauge the bond strengths between the apical hydrogen atoms the negative of the Crystal Orbital Hamilton Population integrated to the Fermi level (À iCOHP) was calculated for the H a À H a pairs.…”
Section: Properties At Ambient Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…CG was deposited either by pipette or by using a previously published airbrush application method. 17 Although lanthanide chemistry is a fairly specialist field, there are a number of emerging applications in areas such as proteomics, 18 organometallic and co-ordination chemistry, 19 superconducting materials 20 and in nuclear medicine. 21 Lanthanide salts are readily available and easily handled (apart from promethium which is radioactive) and as such are good candidates as proxies for other more toxic heavy metals as well as for the actinides (many of which are radioactive).…”
Section: Introductionmentioning
confidence: 99%